1990
DOI: 10.1182/blood.v76.9.1845.1845
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rosetting, cytoadherence, and microagglutination properties of Plasmodium falciparum-infected erythrocytes from Gambian and Tanzanian patients

Abstract: To understand the molecular mechanisms that lead to sequestration of red blood cells infected with mature stages of Plasmodium falciparum and to examine the relevance of earlier studies on adherence properties of laboratory-derived P falciparum parasites to the natural parasite population, we analyzed Gambian and Tanzanian isolates for in vitro cytoadherence and antibody-mediated microagglutination. Eighteen cryopreserved isolates of ring-stage parasites were cultured for 20 to 30 hours in vitro, in the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…However, both the extent and the strength of cytoadherence between the iRBC and endothelial cells were observed to be extremely low in physiological flow conditions. However, coexpression of rosetting and cytoadherence receptors on the same P. falciparum iRBC, as observed in some clinical studies (Hasler et al, 1990), suggests that an individual iRBC can express multiple surface ligands simultaneously. Other recent studies have also implicated certain members of STEVOR and RIFIN variant antigen families in mediating the rosetting of the P. falciparum parasite (Goel et al, 2015;Niang et al, 2014) in a PfEMP1-independent manner.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, both the extent and the strength of cytoadherence between the iRBC and endothelial cells were observed to be extremely low in physiological flow conditions. However, coexpression of rosetting and cytoadherence receptors on the same P. falciparum iRBC, as observed in some clinical studies (Hasler et al, 1990), suggests that an individual iRBC can express multiple surface ligands simultaneously. Other recent studies have also implicated certain members of STEVOR and RIFIN variant antigen families in mediating the rosetting of the P. falciparum parasite (Goel et al, 2015;Niang et al, 2014) in a PfEMP1-independent manner.…”
Section: Discussionmentioning
confidence: 89%
“…To test whether STEVOR proteins were capable of forming rosettes under flow conditions, microfluidics-based rosetting assays were established with R+ sets of 5A, A4, and A4(tr-I and II) clones. As the late-stage iRBC in P. falciparum sequester in blood vessels and disappear from circulation (Hasler et al, 1990;Rowe, Obiero, Marsh, & Raza, 2002), it is reasonable to assume that rosette formation in flow conditions is initiated around these adhered iRBC. Hence, a similar in vitro environment was replicated in our flow-rosetting assays.…”
Section: Stevor Mediates Robust Rosetting In Physiological Flowmentioning
confidence: 99%
“…Almost all isolates bind in vitro to CD36 and thrombospondin (2,5,22,29), whereas only a few isolates adhere to ICAM-1, vascular endothelial cell adhesion molecule, E-selectin, platelet/endothelial cell adhesion molecule 1/CD31, and CSA (4,5,22,25,28,30). Many studies have found no correlation between the cytoadhesion phenotypes of field isolates and the severity of the disease (5,14,15,19,24,30). However, Ho et al found that cytoadhesion to C32 cells was associated with the severity of the clinical case (16), and Newbold et al found a correlation between adhesion to ICAM-1 and clinical illness in nonanemic patients and a particularly strong correlation in cerebral malaria patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…The role and relative importance of these different receptors in sequestration in vivo is not clear, however several lines of evidence indicate a central role for CD36. For example, PRBCs from malaria‐infected individuals from different geographical areas either bind more commonly or at higher levels to CD36 than to other receptors (Hasler et al ., 1990; Ho et al ., 1991; Ockenhouse et al ., 1991; 1992; Cooke et al ., 1995; Newbold et al ., 1997). In a number of studies, development of more severe clinical complications most closely correlated with increased adhesion to CD36 than to other receptors (Ho et al ., 1991; Ockenhouse et al ., 1991; Ringwald et al ., 1993).…”
Section: Introductionmentioning
confidence: 99%